Health Investments and Economic Growth : Macroeconomic Evidence and Microeconomic Foundations - Jack, William (2012)
This paper reviews the correlations and potential links between health and economic growth and summarizes the evidence on the role of government in improving health status. At the macroeconomic level, the evidence of an impact of health on growth remains ambiguous due both to difficulties in measuring health, and to the methodological challenges of identifying causal links. The evidence on the micro linkages from health investments to productivity and income are robust. Progress in life expectancy over the past two centuries has been spectacular, fueled by: improved agriculture that has increased food quantity; knowledge of disease transmission, and effective public health interventions that have controlled communicable diseases such as malaria, yellow fever, and hookworm; and, most recently and importantly, investments in very young children that pay off in healthier and more productive adults. Whether public investments in medical care affect health hinges on the quality of health institutions. In much of the developing world, factors such as chronic absenteeism among public providers, poor budget execution, ineffective management, and virtually no accountability weaken public efforts. Institutional issues are central in efforts to enhance public health investments, which in turn have a direct impact on the population's welfare and, perhaps over the long term, improvements in national income.